Diversity and uses of ethno-medicinal plants associated with traditional agroforestry systems in Kumaun Himalaya - PARIHAAR, RAJENDRA S; BARGALI, KIRAN; BARGALI, SURENDRA S (The Indian Journal of Agricultural Sciences, 2014)
Uttarakhand state is bestowed with great diversity of medicinally important plants which are used frequently by the local people/inhabitants to cure various ailments in their daily life. Traditional agroforestry is a common land use pattern in Uttarakhand which supports various indigenous medicinal plants. The present study provides comprehensive information on the diversity and utilization of medicinally important plants in existing traditional agroforestry systems. The information was gathered using semi-structured questionnaires about the types of ailments treated by the traditional use of medicinal plants, preparation of herbal medicine and formulations. A total of 68 plant species belonging to 38 families and 63 different genera, were reported from agroforestry systems of this region. The families; Rosaceae, Asteraceae, and Verbenaceae were represented by more than 3 species each and dominated the floral composition while remaining 35 families were represented by single species. Different plant parts such as roots/rhizomes/bulbs, leaves, bark, fruits, seeds, flowers, stem and whole plant were used for the treatment of various diseases.